Improvement design of solar chimney - Tey, N.W (Universiti Malaysia Sarawak, UNIMAS, 2009)
Renewable energy has become more preferable to the society compare with conventional energy. This project presents the design, fabrication and performance analysis of the improved solar chimney power generator. The solar chimney apply hot air rise concept to generate power. The design consists of a chimney tower connected on top of the circular solar collector with a chimney support. Within the chimney tower lie two generators, one above another to generate power. Below of the solar collector lays the heat absorber tiles and water tubes. The water tubes absorb heat during the day time, and release the heat during the night for the power generation. An air flow director is placed below the chimney tower to direct the air into the tower and then turn the electrical generators. In this project, air flow simulation and fabrication method were employed. The performance of the solar chimney is dependent to the solar radiation, solar collector’s size, chimney tower’s height, collector’s transparency and type of heat absorber. The night operation performance is dependent on the water tube and heat absorber type. The solar chimney is 4.2 meter diameter and 3.6 meter height. The simulation will simulate the air behaviors within the solar chimney.